Indonesia's Defense Diplomacy to Strengthen National Airspace: A Study of the F-16 Fighter Upgrade - Isnawan, Rudy; Dermawan, Windy (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2024)
This paper aims to analyze Indonesia's efforts through Indonesian defense diplomacy towards the US to optimize its air defense with the F-16 A/B Fighter eMLU (enhanced Mid-Life Upgrade) program. In facing the rapid development of military technology and potential threats from other countries, a defense equipment modernization program, increased personnel training, and the development of more integrated radar infrastructure and air defense networks are absolutely necessary to be able to carry out air defense functions optimally and effectively, and protect the sovereignty of Indonesia's airspace from various potential threats. However, in reality, Indonesia's air power is still faced with various obstacles, one of which is that the F-16A/B fighter aircraft currently owned by Indonesia is not optimal to match the strength of other countries' aircraft. To optimize this, modernization and improvement of weapons for the F-16 Fighter Aircraft are very important. The researcher uses the Defense Diplomacy Concept according to Cottey and Forster. The research was conducted using a qualitative method with data collection through interviews, internet-based research and literacy studies. The results of the research show that Indonesia's defense diplomacy towards the US is carried out through several instruments, military education and training, military meetings and dialogues, humanitarian missions, and military cooperation.